Acute SARS‐CoV‐2 alpha variant infection leading to placental insufficiency and fetal distress. Issue 3 (12th October 2021) - Dumont, Sander; Balduyck, Jonas; Reynders, Marijke; Vanwalleghem, Lieve; Lebbe, Barbara
Abstract: The effect of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) Alpha variant (also known as B.1.1.7 lineage, 20I/501Y.V1, the UK variant or VOC 202012/01) infection on pregnancy is currently unknown. We present a case of a 37‐year‐old woman admitted to our tertiary hospital at a gestational age of 29 weeks and 1 day because of oligohydramnios with reduced fetal movements for 10 days. About 20 days before admission, she tested positive for SARS‐CoV‐2 Alpha variant. The following day, due to abnormal cardiotocography, increased brain sparing, and absent end‐diastolic flow in the umbilical artery, an urgent cesarean section was performed. The neonate had an uneventful admission to the neonatal intensive care unit. All neonatal samples proved negative for SARS‐CoV‐2. Pathological examination of the placenta revealed intervillous fibrin deposition, ischemic necrosis of villi and histiocytic intervillositis, corresponding with the SARS‐CoV‐2 placentitis triad. The placental tissue demonstrated a high viral load, possibly explaining the acute onset of placental insufficiently and subsequent fetal distress. This case demonstrates the importance of seeking medical care when experiencing reduced fetal movement in SARS‐CoV‐2 infected patients since acute infection can induce significant placental and subsequent fetal pathology.